Pengaruh Degree of Operating Leverage, Degree of Financial Leverage, Degree of Combined Leverage dan Likuiditas Terhadap Profitabilitas - Stephanie Stephanie; Sugeng Priyanto (LPPM Politeknik Pratama, 2026)
This study aims to determine the effect of Operating Leverage, Financial Leverage, Combined Leverage, and Liquidity on Profitability. The data used is secondary data in the form of annual financial reports of companies in the Property and Real Estate sector listed on the Indonesia Stock Exchange for the period 2020-2024. The sample selection used purposive sampling of 33 companies from 90 companies in the Property and Real Estate sector listed on the Indonesia Stock Exchange for the period 2020-2024. The analysis tool used was multiple linear regression, which was tested using the SPSS (Statistical Package for Social Science) version 26 program. The results showed that liquidity had a significant effect on profitability, while the degree of operating leverage, degree of financial leverage, and degree of combined leverage had no effect on profitability.